Mapping the intellectual structure of lead exposure and occupational health research in mining: A bibliometric analysis (2015–2025) - Ismi Farah Syarifah; Rizal Maulana Hasby (CV Rezki Media, 2025)
Background: Lead exposure remains a significant occupational health issue in the mining industry, where workers are frequently exposed to dust, particulate matter, and contaminated environments. While research has increased, the literature often develops in separate thematic streams, making it difficult to capture the overall structure and relationships between key areas of study. Objectives: This study aims to map research trends and thematic developments related to lead exposure and occupational health in the mining industry from 2015 to 2025. The goal is to provide a comprehensive bibliometric overview of the field and identify dominant and emerging themes. Methods: A bibliometric approach was applied using Scopus-indexed publications. Peer-reviewed articles and review papers published between 2015 and 2025 were screened for relevance, resulting in a dataset of 133 documents. Descriptive analyses examined publication trends, subject areas, document types, leading journals, authors, affiliations, and contributing countries. Keyword co-occurrence analysis was performed using VOSviewer to map thematic patterns. Results: The volume of publications increased significantly after 2020, peaking in the early 2020s. Research predominantly focused on environmental and health-related topics, driven by empirical studies. The thematic mapping revealed three major clusters: (1) mining assessment, (2) epidemiological outcomes, and (3) occupational health risks. Although connections between exposure assessment and health outcomes were observed, these relationships remain weak. Conclusions: Research on lead exposure and occupational health in mining has shown sustained growth and thematic maturity. However, there is limited integration between exposure monitoring and health outcome studies. Future research should focus on integrating exposure monitoring with health outcomes, particularly in high-risk mining sectors.